Znaczenie i funkcja motywu ruty w warmińsko-mazurskich pieśniach ludowych - Lechocka, Ewelina (Motywy fauny i flory w literaturze i kulturze, 2018)
This article is an analysis of rue motives, which occurred in collection of Warmian and Masurian folk songs elaborated in 19th and 20th century. The purpose of this study was to define botanic vocabulary mentioned in folkloristic texts and to compare poetic representation of rue motif with its role in every-day-life and culture of Warmia and Masuria’s inhabitants. As it was deducted from maintained analysis, the folk output and botanic themes are a valuable source of information about identity of rural population from Warmia and Masuria territories. Utilization of rue motif in folksongs is characteristic for its strong resemblance to empiric reality, in which the plant plays a great role in every-day-life and in immaterial culture.